GE_GERICHTE A/907/2016 vom 11. August 2016 - GE Cour de justice (2016)
VICNOT; FORPOU; FORSPE; ELEFOR; RESDEL; NOTVAL; ATTNOT; NOTCDP | LP.33.2; LP.33.4; LP.46; LP.48 à 52; LP.64.1; LP.66.3; CLaH.6.1; CLaH.6.2; CLaH.65.3